Análise do esporte como ferramenta de marketing nas instituições de ensino superior: o caso ULBRA - Lima, Leonardo Silva de (2007)
The sport, with its characteristic of emotional and pleasant involvement with different public, constantly is used in the marketing having involved differentiation, approach with specific customers and searching to develop basic important values for the competitive environment. In such a way, this study it objectified to analyze as the sport was inserted in the institutions of superior education and of that it forms is used in the marketing, through the study of case of the Luterana University of Brazil (Ulbra). It was opted to the conduction of the study of explore form, with analyzes qualitative aiming at to more get deepened information on the subject. Following the orientations of Aaker, Kumar & Day (2001), when if does not have many information on the subject that if it intends to study and the knowledge of the incidence of the problem are scarce, needs a demystification occult factors, that will only be capable to be carried through the exploration of the problem. The option for the case study was considered basic through the story of Yin (2001) when the author describes the case study as a chosen strategy when it examines events contemporaries and if they cannot manipulate excellent behaviors. It was verified that the sport is very bigger a managemental 0 variable of what only one communication channel. Initiate through partnerships with traditional clubs, the sport was inserted in the institutional context as a viable factor for the fortifyment of the mark. In 1998 the Sport Club Ulbra is constituted, involving a proper structure, individualized administration of the institution and proper strategies of marketing. This composition involves the sport in a platform of unit of business for the Ulbra, leading to the agreement of the exchange of intrinsic values between the institution and the club. The sport provides to an improvement in the relationships with the customers and the internal public of the institution, making possible the approach of the sectors and developing the bonds with the same ones. The investments in the sport have translated the growth of the institution and the emphasis in events that are motivated by the overcoming of adversities and pleasant moments becomes it stronger as strategy of institutional marketing. The importance of this activity legitimizes the organization as promotional of concepts of health, victories and education, factors that are basic for the social recognition of the mark. After this theoretical understanding, perceives that the institution obtains to keep on factors in its planning, searching in the sport a source of affinities capable to interact with the customers through pleasant moments involving social emotions, symbologies, representatives and organizational competitiveness. Thus, the relation with the sport fortifies the mark in a social context and if it ahead gets competitive advantages of the market, making with that the institution is an icon with respect to union between the sport and the marketing